Effect of different water pH on hatching and survival rates of African catfish Clarias gariepinus (Pisces: Clariidae) - Kasi Marimuthu; Harysooria Palaniandya; Zainal A. Muchlisin (Syiah Kuala University, 2019)
Water quality parameters influence the growth and survival of different stages of fishes and hence determining the optimal water quality variables is greatly important for any aquaculture farming. Among the variables, water pH is considered the key factors and plays an important role in the maintenance of the homeostasis in fishes. A study was conducted to determine the influence of different water pH on the incubation period, hatching rate and survival rate of African catfish (Clarias gariepinus) larvae. The fertilized eggs were incubated at 28.0 ± 1.0 °C with different levels of water pH ranging from 3-10. Twenty four pH levels were tested for incubation period and egg hatchability while 15 pH levels were tested for larval survivability in a completely randomized design with three replicates for each treatment. Just hatched larvae were used for this study and the effect was observed until 72 h post-hatching. Water pH was maintained by the addition of NaOH or H2SO4solutions. The incubation times of fertilized eggs were recorded to be 23.5–25.0 h at pH levels of 6.1–8.8. The increased incubation time was noticed at the rest of the acidic and alkaline pH levels. Significantly highest hatching rate was observed at the pH levels of 6.7–7.6 compared to those at lower and higher pH levels (P0.05). However, no significant differences (P0.05) were recognized in the hatching rates at the pH levels of 6.7 – 7.6. No hatching occurred at low pH levels between 3.1 and 3.4 and at high pH of 10. After 72 h of exposure to different pH levels, no larvae survived at pH levels below 4.5 and above 9.0. Highest larval survival (98%) was observed at pH 7.0 followed by 94% at pH 7.5 and 92% at pH 6.5. The results obtained in the present study revealed embryos and larvae can survive and tolerate to a low pH level of 3.7 and 4.5, respectively but the survival rates decreased with decreasing pH levels. Therefore, a water pH level of 6.7–7.5 is highly recommended for optimal hatching and highest larval viability of C. gariepinus.